Predição de falhas em redes de grades OBS com plano de controle GMPLS - BECHARA, Mariana Castro (Universidade Federal do Pará, 2013)
This paper presents a proposal for predict failures in OBS grid network with GMPLS to assist applications in collaborative environments, like E-Science. Agents monitoring traffic (DQMA-Fuzzy) for related QoS parameters and others related to imperfections in optical links. A system based on fuzzy logic has been developed to give more robustness and flexibility in decision-making agents, because it presents a solution faster and easily implementable. NS-2 (Network Simulator – 2) simulations show that the proposed DQMA-Fuzzy is able to minimize blockages and balancing the use of grid resources, ensuring well-defined service levels, assisting in traffic engineering and fault prediction.